The Use of The Drill Method In Overcoming Students’ Learning Difficulties In Class IX Islamic Religious Education Materials of SMPN 17 Kendari - LA HAMIKU (International Journal of Management and Education in Human Development, 2023)
This study aims to: 1) obtain confirmation is drill method can overcome difficulty Study material Islamic religious education student class IX SMPN 17 Kendari. Method of collecting the data start method observation, measurement test results learning. Method of data collecting was using the data from the results of students’ test, the state of the teacher, the situation participant students, PAI curriculum, and so on. Test is something thenik or the method used in framework carry out activity measurement, which is from various question, question or series task to be done or answered by participants educate for measure aspect behavior participant educate. Test implemented in class IX Senior High School 17 Kendari. Collected research data then analyzed, and results analysis the showed that there is enhancement ability read student from before applying drill method and after applied drilling method.